The Influence of the Teachings of Persaudaraan Setia Hati Terate (PSHT) on Adolescent Character Formation in Totokaton Village, Punggur District - Suryadi Armanto; Hernisawati Hernisawati; Choirudin Choirudin (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to analyze the influence of the teachings of the Persaudaraan Setia Hati Terate (PSHT) pencak silat organization on the character formation of adolescents in Totokaton Village, Punggur District, Central Lampung. The research employed a qualitative method with a sociological approach through interviews, observations, and documentation. The results indicate that PSHT teachings, which are based on the Panca Dasar (brotherhood, sports, self-defense, arts, and spirituality), play a significant role in fostering discipline, responsibility, solidarity, and spirituality among adolescents. Participation in PSHT activities, such as martial arts training, religious gatherings, community service, and social visits, has proven to reduce deviant behaviors while enhancing social awareness. In conclusion, PSHT functions not only as a platform for physical development but also as an effective means of character education for young people, contributing positive to the social life of the village community